Churchill and the Islamic World : Orientalism, Empire and Diplomacy in the Middle East - Dockter, Warren (London I. B. Tauris, 2016)
Winston Churchill began his career as a junior officer and war correspondent in the North West borderlands of British India, and this experience was the beginning of his long relationship with the Islamic world. Overturning the widely-accepted consensus that Churchill was indifferent to, and even contemptuous of, matters concerning the Middle East, this book unravels Churchill's nuanced understanding of the edges of the British Empire. Warren Dockter analyses the future Prime Minister's experiences of the East, including his work as Colonial Under-Secretary in the early 1900s, his relations with the Ottomans and conduct during the Dardanelles Campaign of 1915-16, his arguments with David Lloyd- George over Turkey, and his pragmatic support of Syria and Saudi Arabia during World War II.
Include Bibliography and Index
Keywords: Churchill, Winston, -- 1874-1965 -- Knowledge -- Middle East -- Churchill, Winston -- (Winston Leonard Spencer), -- 1874-1965 -- Churchill, Winston, -- 1874-1965